Pengaruh Positive Word of Mouth, Perceived Value dan Digital Marketing terhadap Kepuasan Pelanggan Jasa Ekspedisi Wahana Express - Hidayat, Farid (Yayasan Lentera Avanya Nagari, 2025)
This research aims to analyze the influence of positive word of mouth, perceived value, and digital marketing on customer satisfaction with the Wahana Express expedition service. The sample in this research was 100 respondents who had used Wahana Express services online. The data collection technique used was a survey with the research instrument used was a questionnaire. The results of the instrument test stated that the data in this study was proven to be valid and reliable. The Classical Assumption Test stated in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The results of this research prove that: (1) Positive Word of Mouth has a positive and significant effect on Customer Satisfaction of Wahana Express Expedition Services, (2) Perceived Value has a positive and significant effect on Customer Satisfaction of Wahana Express Expedition Services, (3) Digital Marketing has a positive and significant effect on Customer Satisfaction of Wahana Express Expedition Services. significant impact on Customer Satisfaction with Wahana Express Expedition Services. The results of this research have implications for further research to examine in more depth other variables that can influence the level of customer satisfaction with the Wahana Express expedition service.